Exploring the pathways of social organization participation in China's vaccine immunization efforts - Ziwen XU; Xin ZHENG; Lanlan ZHAO; Ren CHEN (Editorial Office of Chinese Journal of Public Health, 2024)
Social organizations, which exist outside of governmental and market systems, are vital actors in social governance. Investigating the pathways through which social organizations participate in vaccination and immunization efforts can significantly contribute to the advancement of immunization programs. This paper elaborates on the practical need, theoretical basis, and policy support for social organizations' involvement in vaccination and immunization activities. It identifies various challenges faced by these organizations, including incomplete collaborative mechanisms, limited societal recognition, and intrinsic organizational shortcomings. Furthermore, the paper explores strategies for enhancing social organizations' participation in vaccination and immunization work, such as strengthening public education, providing consultation and advice, supporting grassroots immunization efforts, offering psychological assistance, linking social resources, and aiding in quality assurance. Recommendations are proposed with the aim of providing a reference for the efficient involvement of social organizations in vaccination and immunization activities.